Characterization of Ripening-Regulated cDNAs and Their Expression in Ethylene-Suppressed Charentais Melon Fruit - Hadfield, Kristen A. (American Society of Plant Biologists, 2000)
Charentais melons (Cucumis melo cv Reticulatus) are climacteric and undergo extremely rapid ripening. Sixteen cDNAs corresponding to mRNAs whose abundance is ripening regulated were isolated to characterize the changes in gene expression that accompany this very rapid ripening process. Sequence comparisons indicated that eight of these cDNA clones encoded proteins that have been previously characterized, with one corresponding to ACC (1-aminocyclopropane-1-carboxylic acid) oxidase, three to proteins associated with pathogen responses, two to proteins involved in sulfur amino acid biosynthesis, and two having significant homology to a seed storage protein or a yeast secretory protein. The remaining eight cDNA sequences did not reveal significant sequence similarities to previously characterized proteins. The majority of the 16 ripening-regulated cDNAs corresponded to mRNAs that were fruit specific, although three were expressed at low levels in vegetative tissues. When examined in transgenic antisense ACC oxidase melon fruit, three distinct patterns of mRNA accumulation were observed. One group of cDNAs corresponded to mRNAs whose abundance was reduced in transgenic fruit but inducible by ethylene treatment, indicating that these genes are directly regulated by ethylene. A second group of mRNAs was not significantly altered in the transgenic fruit and was unaffected by treatment with ethylene, indicating that these genes are regulated by ethylene-independent developmental cues. The third and largest group of cDNAs showed an unexpected pattern of expression, with levels of mRNA reduced in transgenic fruit and remaining low after exposure to ethylene. Regulation of this third group of genes thus appears to ethylene independent, but may be regulated by developmental cues that require ethylene at a certain stage in fruit development. The results confirm that both ethylene-dependent and ethylene-independent pathways of gene regulation coexist in climacteric fruit.